Zmiana nazwiska rodzica po rozwodzie a nazwisko dziecka - Haberko, Joanna (Studia Prawa Publicznego, 2022)
The text takes up the problem of the role of names in human life. The author refers to the identifying and ordering role of each person’s name in legal relations; she recognizes that the surname is a personal right and, moreover, that it is part of the marital status disclosed in marital status records. The surname also indicates the particular familylegal relationship of a person, both in terms of being married and being descended from certain parents. The text relates ﬁrst of all to the method of establishing the surname for a child coming from spouses, and then to the child’s situation in the face of their parents’ divorce and of using the possibility of returning to the surname before marriage. The choice of the child’s name is not arbitrary. The Act regulates in detail the method and timing of selecting a child’s name. As a rule, in the case of a spouse’s child, the child’s surname remains associated with the presumption of descent from the mother’s husband. The article goes on to deal with the issue of the surname being changed by the parents following a divorce and the lack of inﬂuence of this decision on a change in the child’s surname. When a parent decides to return to their pre-marriage surname, they exercise their own right, the effects of which do not extend to the child. The author analyzes the impact of changing the parent’s surname in connection with entering into a new marriage, as well as the admissibility of changing the surname under administrative procedure, extending these effects to the situation of the minor’s surname. The text indicates a number of factors from which the law makes it possible to change a child’s surname. In the discussion, the author comes to the conclusion that changing a surname in the administrative mode remains independent of the situations indicated in the Family Code, which means that it should take place only exceptionally and solely for important reasons.